2008
DOI: 10.1111/j.1365-3059.2007.01791.x
|View full text |Cite
|
Sign up to set email alerts
|

Melon yellow spot virus in watermelon: a first record from Taiwan

Abstract: During April 2007, systemic necrotic spots were observed on melon ( Cucumis melo ) grown in plastic greenhouses in Haimen city of Jiangsu Province, China. By mid May disease rates in different plastic houses ranged from 19 to 100% with symptoms characteristic of Melon necrotic spot virus (MNSV). These symptoms included many necrotic spots on the young leaves followed by coalescence of spots to form larger irregular lesions on older leaves. Necrotic stripes appeared on stems, and the infected leaves also became… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…At least seven RNA viruses (Chen et al 2008;Huang et al 1993) including CGMMV, CMV, Melon veinbanding mosaic virus, Melon yellow spot virus, PRSV-W, WSMoV and ZYMV, and one DNA virus, SLCPHV (Tsai et al 2007) have been reported to infect cucurbit plants in Taiwan. New virus-like symptoms of mosaic, leaf curl and puckering were observed on C. melo var.…”
Section: Discussionmentioning
confidence: 99%
“…At least seven RNA viruses (Chen et al 2008;Huang et al 1993) including CGMMV, CMV, Melon veinbanding mosaic virus, Melon yellow spot virus, PRSV-W, WSMoV and ZYMV, and one DNA virus, SLCPHV (Tsai et al 2007) have been reported to infect cucurbit plants in Taiwan. New virus-like symptoms of mosaic, leaf curl and puckering were observed on C. melo var.…”
Section: Discussionmentioning
confidence: 99%
“…MYSV was first detected on melon (Cucumis melo) in Shizuoka Prefecture in 1992 (Kato et al 2000), on cucumber (C. sativus) in Kochi Prefecture in 1995 (Takeuchi et al 2001), and on balsam pear (Momordica charantia) in Kochi Prefecture in 2007 (Takeuchi et al 2009). MYSV has become the prevalent virus of cucumber in the Kyusyu and Shikoku regions and has also been reported in Taiwan and Thailand (Chen et al 2008;Chiemsombat et al 2008). MYSV induces chlorotic spots, mosaic mottling, yellowing on leaves, and mosaic patches on fruits of melon, and sometimes causes mottling on fruits of cucumber.…”
Section: Introductionmentioning
confidence: 98%
“…The areas affected by MYSV are increasing, especially in the Kyushu, Shikoku, Tokai, and Kanto regions of Japan. In addition, MYSV has also been reported in Taiwan, Thailand, and China (Chen et al, 2008;Chiemsombat et al, 2008;Gu et al, 2012). The virus induces chlorotic spots, mosaic mottling, and yellowing on the leaves, and sometimes causes mottling on fruits.…”
Section: Melon Yellow Spot Virus-resistant Cucumbermentioning
confidence: 99%